Pendampingan Peningkatan Kapasitas Produksi dan Pemasaran Kunyit Asam, Jahe Instan, Fatis, Melalui Teknologi Mesin Modern - Muntasir Muntasir; Sigit Purnawan; Dimas Rohman Ardiansyah; Iffah Atiqah Sari; Gusnawati Gusnawati (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This program aimed to enhance the quality, production capacity, and marketing of herbal products (turmeric-tamarind drink, instant ginger, and fatis) at the NTT Herbal Lab MSME by integrating a rhizome processing machine with digital marketing support. Methodology: Implemented in Kupang City, the intervention combined: (1) training on operating a slicing/crushing machine, (2) mentoring in Good Manufacturing Practices (GMP), and (3) assistance in digital marketing via Instagram, Facebook, Shopee, and Tokopedia. Results: Results showed significant gains, with production efficiency rising 80-100%, production time halved, and sales turnover increasing by 98% within six months. This was supported by a minimum 30% sales growth resulting from expanded digital reach. Product quality and consistency also improved. Conclusions: The integration of appropriate technology and digital strategy effectively empowered the MSME. This holistic model, which also aids local wisdom preservation, is recommended for adaptation by similar herbal enterprises. Limitations: The study's scope was limited to a single MSME, indicating potential for further refinement of both the production technology and marketing strategies. Contributions: This study provides a practical, replicable model for community empowerment, contributing to the development of appropriate technology, and enhanced market access for the herbal industry in Eastern Indonesia.